2006
DOI: 10.1007/s10517-006-0306-x
|View full text |Cite
|
Sign up to set email alerts
|

Cell transplantation inhibits inflammatory reaction and stimulates repair processes in burn wound

Abstract: We compared the effects of transplantation of fetal fibroblasts and fibroblast-like mesenchymal stem cells of the bone marrow on healing of deep burn wound in rats. It was found that transplantation of fetal fibroblasts and fibroblast-like mesenchymal stem cells on the burn surface reduces cell infiltration, promotes the formation of vessels and granulation tissue, which creates conditions for more rapid healing of the burn wounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 12 publications
0
21
0
1
Order By: Relevance
“…This capacity makes them promising candidates for use in regenerative medicine. Human and animal studies have shown that MSCs have potential to repair bone [12,13], cartilage [14,15], skin [16,17], and neuronal tissue [18] and improve the function of cardiac muscle [19–21] and the kidney [22]. Recent clinical trials are investigating the use of MSCs in treating heart disease, liver cirrhosis and bone fractures.…”
Section: What Is Already Known?mentioning
confidence: 99%
“…This capacity makes them promising candidates for use in regenerative medicine. Human and animal studies have shown that MSCs have potential to repair bone [12,13], cartilage [14,15], skin [16,17], and neuronal tissue [18] and improve the function of cardiac muscle [19–21] and the kidney [22]. Recent clinical trials are investigating the use of MSCs in treating heart disease, liver cirrhosis and bone fractures.…”
Section: What Is Already Known?mentioning
confidence: 99%
“…Because burn wound is convenient for local application in most of the reviewed studies MSCs have been transplanted by local injection wound or peri-wound area or topical dripping. Some authors have chosen topical dripping of the stem cells onto burn wound [44,48]. Although burn wound is accessible for local dripping of MSCs, because of uncontrollable nature of cell suspensions, the engraftment efficiency can be varied by dripping.…”
Section: Delivery Methods Of Mscs In Burn Wound Studymentioning
confidence: 99%
“…Singer et al [46] used same amount of cells for the larger stasis zone. Rasulov et al [48] have reported accelerated wound healing by using only 200 cells/cm 2 . Fu et al [47] have showed beneficial effect of MSC on burn wound healing in 2 Â 10 5 cells/cm 2 .…”
Section: Therapeutic Dose Of Mscs In Burn Wound Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Adult stem cell therapy reduces the intensity of inflammatory cell infiltration and activates the vessel formation. Thus, it promotes normal interactions between cell assemblies during the regeneration of burn wounds, which prevents the formation of cicatrix or the deformation of tissues [24,25].…”
mentioning
confidence: 99%